Enhancing Seafarers’ Self-Awareness and Emergency Decisions through Bridge Simulator Training - Supangat; Sriantini, Ari (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2026)
This study examines the association between Bridge Simulator training, seafarers’ self-awareness, and emergency decision-making performance. A quantitative correlational design was employed involving 105 active seafarers who had participated in certified bridge simulator training. Data were collected using a structured questionnaire measuring perceived training quality, self-awareness, and emergency decision-making performance. Spearman’s rho correlation analysis revealed a strong positive association between Bridge Simulator training and self-awareness (ρ = 0.764), as well as between Bridge Simulator training and emergency decision-making performance (ρ = 0.744). These findings indicate that higher perceived quality of simulator training is associated with higher levels of self-awareness and decision-making performance in emergency contexts. The study contributes empirical evidence on the psychological and cognitive dimensions associated with simulator-based maritime training and highlights implications for maritime education and safety training.